Product performance evaluation using CAD/CAE - Chang, Kuang-Hua (Computer aided engineering design series, 2013)
This is one book of a four-part series, which aims to integrate discussion of modern engineering design principles, advanced design tools, and industrial design practices throughout the design process. Through this series, the reader will: Understand basic design principles and modern engineering design paradigms; Understand CAD/CAE/CAM tools available for various design related tasks; Understand how to put an integrated system together to conduct product design using the paradigms and tools; Understand industrial practices in employing virtual engineering design and tools for product development